Persistent Neovascular Exudation in Patients with Exudative Age-Related Macular Degeneration who have Choroid Imaging Biomarkers of Non-Neovascular Choroidal Pathology: Simultaneous Choroidal Hyperpermeability and Angiogenesis - Mark H. Nelson; William Sanfelippo (Journal of Ophthalmic Science, 2025)
Purpose Create a new diagnostic and therapeutic framework for patients with Exudative Age-Related Macular Degeneration (ARMD) and choroid imaging biomarkers of non-neovascular choroidal pathology who have persistent neovascular exudation during the course of monotherapeutic interventions. Methods Retrospective, longitudinal case series study of 25 eyes from 23 patients with the referral diagnoses of treatment resistant Exudative ARMD who had persistent neovascular exudation despite various monotherapies. Inclusion criteria required choroidal imaging biomarkers of non-neovascular pathology including a thickened subfoveal choroid (greater than 300 microns) and vessels (subjectively dilated choroidal vessels in Haller’s layer) on Optical Coherent Tomography (OCT), choroidal neovascularization on IVFA and OCT Angiography (OCTA), as well choroidal leakage noted on indocynanine green videoangiography (ICG). Treatment consisted of OCTA and ICG - Directed Photodynamic Therapy (PDT) Triple Therapy, hereafter described as Combination Therapy, to areas of choroidal hyperpermeability and choroidal neovascularization. Combination therapy consisted of an anti-Vascular Endothelial Growth Factor (VEGF) intravitreal injection on Day 0 followed by half-fluence PDT and 2 mg intravitreal triamcinolone acetonide on Day 3-14. Results All study patients had treatment resistant Exudative ARMD defined as persistent subretinal and/or intraretinal fluid during their course of monotherapeutic interventions. Complete resolution of all exudation occurred in 23 eyes (92.0%) at 8 weeks. The mean duration of action was 155.6 weeks, with 72.0% of eyes leak free greater than 100 weeks. The mean vision at baseline was 0.46 ± 0.42 LogMAR, best corrected visual acuity (BCVA). 8 weeks after treatment, the vision was 0.35 ± 0.38 LogMar, an improvement of over one line, and this was maintained at one year. The baseline central subfield thickness (CST) was 296.4 ± 136.1 microns and improved by 111.4 ± 105.4 microns at 8 weeks after treatment. Treatment duration was negatively associated with the Caucasian race. Conclusions Patients with subretinal and/or intraretinal fluid secondary to Exudative ARMD should have a complete baseline multimodality imaging study to confirm the presence of neovascularization and whether choroidal hyperpermeability coexists. This study shows that patients with Exudative ARMD and persistent neovascular exudation despite monotherapuetic interventions often have choroidal biomarkers of non-neovascular choroidal pathology and that ICG and OCTA-directed PDT Triple Therapy resulted in complete resolution of all exudation in 92.0% of patients at 8 weeks with a reduction in central subfield thickness (CST) of 111.4 microns. The vision improvement at 8 weeks was 0.11 ± 0.38 LogMar and was sustained over 1 year. The mean duration of action was 155.6 weeks, with 72.0% of eyes leak free greater than 100 weeks. Additionally, this study shows that the treatment that addresses both pathological processes is successful and should be considered as a primary protocol when the biomarkers are present at baseline or as a secondary protocol if indeed the neovascular leakage is persistent despite monotherapy. Summary Patients with an Exudative ARMD with persistent neovascular exudation despite anti-VEGF monotherapy and who have imaging biomarkers of non-neovascular choroidal pathology often have two pathophysiological processes: choroidal hyperpermeability and angiogenesis. A proposed framework provides the rationale for OCTA and ICG-directed PDT Triple Therapy which successfully resolves 92% of the leakage that was persistent after various monotherapeutics.
Keywords: Choroid